An idea which yields a lot of elementary inequalities - Szalay, István (Teaching Mathematics and Computer Science, 2010)
The aim of the article is to show how studies in higher mathematics can be applied in everyday teaching practice to construct new problems for their pupils. In higher mathematics it is known that the set of real numbers with the addition and multiplication (shortly: (R,+,x)) is an ordered field. Considering a strictly monotonic increasing and continuous function σ with domain ...By this idea, using different kinds of functions σ we show a lot of different elementary inequalities.